Selection of Retapamulin, a Novel Pleuromutilin for Topical Use - Rittenhouse, Stephen (American Society for Microbiology, 2006)
The in vitro activity of retapamulin was determined and compared to that of topical and community antibiotics. The MIC(90)s of retapamulin against Staphylococcus aureus and Streptococcus pyogenes were 0.12 μg/ml and 0.016 μg/ml, respectively. Retapamulin has a low propensity to select resistance and produces an in vitro postantibiotic effect.